Synthesis of Polyfluorinated Thia- and Oxathiacalixarenes Based on Perfluoro-m-xylene - Vladimir N. Kovtonyuk; Yuri V. Gatilov; Pavel V. Nikul’shin; Roman A. Bredikhin (Molecules, 2021)
Perfluorinated tetrathiacalix[4]arene was obtained by heating perfluoro-m-xylene with thiourea or 2,5-difluoro-4,6-bis(trifluoromethyl)benzene-1,3-dithiol at 90 °C. Interaction of perfluoro-m-xylene with resorcinol or orcinol under mild conditions and subsequent heating of the mixture with 2,5-difluoro-4,6-bis(trifluoromethyl)benzene-1,3-dithiol leads to polyfluorinated dioxadithiacalix[4]arenes. Triphenyl and pentaphenyl ethers formed by the interaction of perfluoro-m-xylene with resorcinol under heating with thiourea gives polyfluorinated oxathiacalixarenes containing six and five aromatic nuclei, respectively.